2015
DOI: 10.1080/00380768.2015.1086279
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and nitrogen fixation potential ofBradyrhizobiumspecies isolated from the legume cover cropPueraria phaseoloides(Roxb.) Benth. in Eastern Cameroon

Abstract: Pueraria is an herbaceous, perennial legume crop originating in Asia. Pueraria phaseoloides (Roxb.) Benth. (tropical kudzu) is frequently introduced into production systems and is used as green manure, a cover crop and a forage plant, making it important economically. We used P. phaseoloides as a trap crop to study and characterize soil rhizobia in Eastern Cameroon. Bacteria were isolated from fresh nodules collected from field-grown P. phaseoloides roots. The 16S-23S rRNA internal transcribed spacer (ITS) seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…Thus, core microbiomes need to be elucidated for major crops from diverse agricultural regions of the world because abiotic factors, soil geochemistry, and water availability all have a powerful influence on plant diversity and microbial populations. Efforts to learn more about indigenous rhizosphere microbiomes are being pursued in several countries, including Pakistan (Mukhtar et al 2016), Cameroon (Sarr et al 2016), and Sudan (Idris et al 2015). It will also be interesting to determine whether various microbes are conserved in similar environments.…”
Section: Do Nonrhizobial Bacteria Residing Within the Nodule Influencmentioning
confidence: 99%
“…Thus, core microbiomes need to be elucidated for major crops from diverse agricultural regions of the world because abiotic factors, soil geochemistry, and water availability all have a powerful influence on plant diversity and microbial populations. Efforts to learn more about indigenous rhizosphere microbiomes are being pursued in several countries, including Pakistan (Mukhtar et al 2016), Cameroon (Sarr et al 2016), and Sudan (Idris et al 2015). It will also be interesting to determine whether various microbes are conserved in similar environments.…”
Section: Do Nonrhizobial Bacteria Residing Within the Nodule Influencmentioning
confidence: 99%
“…Prior to this field experiment, rhizobial strains were isolated from Pueraria nodules collected from the experimental site and other neighboring fields and subjected to DNA-based molecular analysis [ 9 ]. The results showed that the native strains for Pueraria in the experimental field clustered into 3 groups corresponding to Bradyrhizobium yuanmingense , B. elkanii , and B. sp.…”
Section: Methodsmentioning
confidence: 99%
“…By assessing their nitrogen fixation potential using the Acetylene Reduction Assay (ARA), it appeared the B. yuanmingense strains, and S3-4 in particular, showed a significant highest potential. Therefore, Bradyrhizobium yuanmingense S3-4 identified as an efficient Pueraria symbiont [ 9 ] was used in this field experiment. From glycerol stock, it was streaked on YMA agar plates [ 24 ] for one week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations